Therapeutic and continuative effects of human umbilical cord–derived mesenchymal stromal cells in food-allergic mice - Yuan Zhao; Yabing Ding; Zhaoyan Wang; Qian Wang; Dou Ye; Zuo Luan (Cell Transplantation)
This study aimed to investigate the impact of human umbilical cord–derived mesenchymal stromal cells (hUC-MSCs) on food allergy (FA) mice induced by ovalbumin. The percentage of regulatory T cells (Tregs) was assessed by administering hUC-MSCs intravenously to FA mouse models with oral challenges, allergic responses and levels of related allergic cytokines. The phenotypes of hUC-MSCs were analysed using flow cytometric analysis. Immunohistochemistry was used for histology observation. Real-time polymerase chain reaction (PCR) was used for gene expression. Jejunum tissue was analysed by transcriptome sequencing. Our results demonstrated that in the current FA model, hUC-MSC therapy significantly alleviated allergic responses and diarrhoea. Levels of immunoglobulin E (IgE), as well as cytokines, such as interleukin (IL)-6 and tumour necrosis factor-α associated with T helper 2 cells, were reduced. Conversely, transforming growth factor (TGF)-β levels increased with hUC-MSC therapy. In addition, enhanced TGF-β expression along with IL-10 messenger ribonucleic acid levels and an increased percentage of CD4 + Foxp3 + Tregs were observed. In long-term FA mice models, hUC-MSC therapy exhibited sustained effects in mitigating rectal temperature decrease and mortality rates while reducing the levels of IgE, IL-6 and proportion of IgE+ cells; it also elevated TGF-β levels. Furthermore, hUC-MSC therapy attenuated pathological injury in both current and long-term FA mouse models. Transcriptome sequencing showed that upregulated differentially expressed genes were mainly concentrated in neural activation–ligand interaction, the cyclic guanosine monophosphate–protein kinase G signalling pathway and the TGF-β signalling pathway. The hUC-MSC therapy holds promise for alleviating both immediate and persistent FA conditions; targeting TGF-β and IL-10 secreted by hUC-MSCs may be a potential approach for treating FA.